Sodium ion battery, battery pack and energy storage system

By using a stabilizer containing (XO4)n-groups in the positive electrode sheet of the sodium ion battery to combine with the sodium ion layered oxide to form a composite positive electrode material, the problem of low cycle life of the sodium ion battery is solved, especially in a high temperature environment, the stability and rate performance of the battery are significantly improved.

CN119786598AActive Publication Date: 2025-04-08HUAWEI DIGITAL POWER TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311298353.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-08
Publication Date
2025-04-08
Estimated Expiration
2043-10-08

AI Technical Summary

Technical Problem

The cycle life of sodium ion batteries is low, especially in high temperature environments, and the cycle life is severely decayed.

Method used

A composite positive electrode material is used, which consists of sodium ion layered oxide as the positive electrode active material. Combined with a stabilizer containing (XO4)n-group, the particle size of the stabilizer is smaller than the particle size of the positive electrode active material to form a continuous conductive network to improve the cycle life of the battery.

Benefits of technology

By improving the conductivity of the positive electrode sheet, the cycle life and rate performance of the sodium ion battery are extended, and it shows higher stability especially in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786598A_ABST
    Figure CN119786598A_ABST
Patent Text Reader

Abstract

The invention provides a sodium ion battery, a battery pack and an energy storage system. The composite positive electrode material comprises a positive electrode active material and a stabilizer, the positive electrode active material is a sodium ion layered oxide, the stabilizer is filled among particles of the positive electrode active material, the particle size of the stabilizer is smaller than that of the particles of the positive electrode active material, and the molecular structure of the stabilizer contains a (XO4) n-group. Wherein X is selected from at least one of P, S or Si, and the atomic percent of X in the composite positive electrode material is 1%-15%. The composite positive electrode material can be used for prolonging the cycle life of the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a sodium ion battery, a battery pack and an energy storage system. Background Art

[0002] Sodium-ion batteries have broad application prospects in the fields of energy storage and low-speed vehicles due to their abundant resources and low theoretical costs. Sodium-ion batteries are mainly composed of four parts: positive electrode materials, negative electrode materials, electrolytes and separators. Among them, the positive electrode material is the most critical material. At present, the positive electrode materials of sodium-ion batteries mainly include layered oxides, polyanion materials and Prussian blue materials. As one of the three major positive electrode materials for sodium-ion batteries, layered oxide materials are considered to be the first sodium-ion battery positive electrode materials to achieve commercial application because of their high gram capacity, simple synthesis process and high compaction density. However, there is a sodium ion deintercalation reaction in the charging and discharging process of layered oxide positive electrode materials. Due to the large radius of sodium ions, the lattice volume of the positive electrode material changes greatly during the charging and discharging process, resulting in a low cycle life of layered oxide sodium-ion batteries, especially in high temperature environments. The cycle life is severely attenuated. Therefore, the cycle stability problem of sodium-ion batteries needs to be solved urgently. Summary of the invention

[0003] The present application provides a sodium ion battery, a battery pack and an energy storage system to improve the cycle life of the sodium ion battery.

[0004] In a first aspect, the present application provides a sodium ion battery, comprising a positive electrode sheet and a negative electrode sheet. The positive electrode sheet comprises a composite positive electrode material, the composite positive electrode material comprises a positive electrode active material and a stabilizer, the positive electrode active material is a sodium ion layered oxide, the stabilizer is filled between particles of the positive electrode active material, the particle size of the stabilizer is smaller than the particle size of the positive electrode active material, and the molecular structure of the stabilizer contains (XO 4 ) n- Wherein, X is selected from at least one of P, S, or Si, and the atomic percentage of X in the composite positive electrode material is 1% to 15%.

[0005] The composite positive electrode material of the positive electrode sheet of the sodium ion battery of the present application is mainly composed of a positive electrode active material and a stabilizer. 4 ) n- The stabilizer with a group has a higher bonding strength with the positive electrode active material and a more stable structure, which can help to improve the cycle life of the battery. In addition, the particle size of the stabilizer is smaller than that of the positive electrode active material. Therefore, a gradation of large and small particles can be formed between the particles of the positive electrode active material and the stabilizer, forming a continuous and reliable conductive network, which helps to improve the conductivity of the positive electrode sheet, thereby improving the cycle life and rate performance of the sodium ion battery.

[0006] In an optional implementation, the median particle size D50 of the stabilizer is 2 Less than or equal to the median particle size D50 of the positive electrode active material 1 A continuous and reliable conductive network can be formed between the particles of the positive electrode active material and the stabilizer, further improving the conductivity of the positive electrode sheet, thereby improving the cycle life and rate performance of the sodium ion battery.

[0007] In an optional implementation, the molecular formula of the positive electrode active material is Na z Ni x M y O 2 , wherein x+y=1, 0.9≤z≤1.1, and M is selected from Fe 2+ , Mn 3+ , Ca 2+ 、Zn 2+ Mg 2+ 、Ti 3+ 、Al 3+ , Cu 2+ The positive electrode active material is a layered oxide material, which can have a higher gram capacity and compaction density, and is helpful to improve the capacity of the sodium ion battery.

[0008] In an optional implementation, the stabilizer is selected from Na 2 Fe 2 (SO 4 ) 3 、Na 2 MSiO 4 、NaFePO 4 、Na 2 FeP 2 O 7 、Na 4 Fe 2 (PO 4 ) 2 O 7 、Na 3 V 2 Fe(PO 4 ) 3 、Na 3 V N 2 Fe(PO 4 ) 3 、Na 3 VTiFe(PO 4 ) 3 、Na 3 Fe 2 Fe(PO 4 ) 3 、Na 3MnTiFe(PO 4 ) 3 The stabilizer has a charge-discharge curve behavior similar to that of the sodium ion layered oxide material and can form a continuous conductive network to improve the conductivity and capacity of the composite positive electrode material.

[0009] In an optional implementation, the median particle size D50 of the stabilizer is 2 The value range is 0.2-2μm.

[0010] In an optional implementation, the gram capacity of the stabilizer is ≥ 60% of the gram capacity of the positive electrode active material, and the median voltage of the stabilizer is within the range of ±15% of the median voltage of the positive electrode active material. The closer the gram capacity of the stabilizer is to the gram capacity of the positive electrode active material, the closer the capacity of the obtained composite positive electrode material is to the capacity of the positive electrode active material, thereby avoiding the reduction of the capacity of the positive electrode composite material due to the addition of the stabilizer.

[0011] In an optional implementation, the mass proportion of the stabilizer in the composite positive electrode material is 1% to 40%. If the amount of stabilizer added is too low, it cannot play a role in forming a conductive network. If the amount of stabilizer added is too high, it will affect the electrical properties of the composite positive electrode material. Therefore, the present application controls the amount of stabilizer added within the above range, so that the composite positive electrode material can obtain better conductivity without reducing the capacity, thereby improving the cycle stability of the sodium ion battery.

[0012] In an optional implementation, the median voltage of the composite positive electrode material is greater than 3.0 V. Optionally, the gram capacity of the composite positive electrode material is greater than 120.0 mAh / g. Optionally, the compaction density of the composite positive electrode material is greater than 3.0 g / cc. Optionally, the film resistivity of the composite positive electrode material is 5 Ω*cm to 30.0 Ω*cm.

[0013] In a second aspect, the present application provides a battery pack, which includes a plurality of batteries, wherein the plurality of batteries are connected in series or in parallel; the battery is a sodium ion battery of the second aspect of the present application.

[0014] In a third aspect, the present application provides an energy storage system, which includes a power converter and at least one battery pack of the third aspect of the present application; the power converter is used to convert the voltage output by the battery pack into power and output it to a power grid or a load, and / or, convert the voltage output by an external power supply into power and output it to the battery pack.

[0015] The technical effects that can be achieved by the second to third aspects mentioned above can be described with reference to the corresponding effects in the first aspect mentioned above, and will not be repeated here.

[0016] Among them, the data in the above possible implementations of the present application, such as the median particle size D50 of the stabilizer 2 , the gram capacity of the composite positive electrode material, the compaction density of the composite positive electrode material, the membrane resistivity of the composite positive electrode material and other data. When measuring, the values ​​within the scope of engineering measurement error should be understood to be within the scope defined in this application. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A schematic diagram of the structure of a sodium ion battery;

[0018] Figure 2 A schematic diagram of the structure of a positive electrode plate;

[0019] Figure 3 This is a cross-sectional scanning morphology photograph of the composite positive electrode material of Example 1;

[0020] Figure 4 This is the energy spectrum of the composite positive electrode material of Example 1;

[0021] Figure 5 It is the charge and discharge curve diagram of the positive electrode material in Comparative Example 1;

[0022] Figure 6 Na is the stabilizer 3 Fe 2 (PO 4 ) 2 O 7 Charge and discharge curve diagram;

[0023] Figure 7 The charge and discharge curves of the composite positive electrode material of Example 1 and the positive electrode material of Comparative Example 1;

[0024] Figure 8 The graph is a cycle capacity retention rate graph of the sodium ion batteries corresponding to Examples 1-3 and Comparative Example 1 at 45°C and 0.5C.

[0025] Reference numerals:

[0026] 11-positive electrode plate; 12-negative electrode plate; 13-diaphragm; 14-electrolyte;

[0027] 111 - positive electrode current collector; 112 - positive electrode material layer; 113 - positive electrode active material; 114 - stabilizer. DETAILED DESCRIPTION

[0028] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings.

[0029] The terms used in the following embodiments are only for the purpose of describing specific embodiments and are not intended to be limiting of the present application. As used in the specification and appended claims of the present application, the singular expressions "a", "an", "above", "the" and "this" are intended to also include expressions such as "one or more", unless there is a clear contrary indication in the context.

[0030] References to "one embodiment" or "some embodiments" etc. described in this specification mean that a particular feature, structure or characteristic described in conjunction with the embodiment is included in one or more embodiments of the present application. Thus, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. that appear at different places in this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways.

[0031] Rechargeable batteries have been widely used in energy storage modules for household energy storage, site energy, smart photovoltaics, and data center energy. As the price of lithium source raw materials continues to rise, sodium-ion batteries have gradually become a research hotspot. However, in sodium-ion batteries, the stability of the positive electrode material and the cycle life restrict the development of sodium-ion batteries. In order to increase the cycle life of sodium-ion batteries, the embodiment of the present application provides a composite positive electrode material in the hope of obtaining a sodium-ion battery with a higher cycle life. In view of the low cycle life of sodium-ion batteries, especially the serious attenuation of high-temperature cycle life, the embodiment of the present application proposes a composite positive electrode material to solve the problem of low cycle life of sodium-ion batteries.

[0032] Figure 1 Figure 1 is a schematic diagram of the structure of a sodium ion battery. Figure 1 As shown, the sodium ion battery includes a positive electrode sheet 11, a negative electrode sheet 12, a separator 13 and an electrolyte 14, the separator 13 is arranged between the positive electrode sheet 11 and the negative electrode sheet 12, and the electrolyte 14 infiltrates the positive electrode sheet 11, the separator 13 and the negative electrode sheet 12.

[0033] Figure 2 Schematic diagram of the structure of a positive electrode. Figure 2 As shown, the positive electrode sheet 11 includes a positive electrode current collector 111 and a positive electrode material layer 112. The positive electrode material layer 112 contains the composite positive electrode material of the embodiment of the present application, and in addition, may also include a binder, a conductive agent, and other additives. Figure 2The composite positive electrode material of the embodiment of the present application includes a positive electrode active material 113 and a stabilizer 114. The positive electrode active material 113 is a sodium ion layered oxide, and its molecular formula is Na z Ni x M y O 2 , wherein x+y=1, 0.9≤z≤1.1, and M is selected from Fe 2+ , Mn 3+ , Ca 2+ 、Zn 2+ Mg 2+ 、Ti 3+ 、Al 3+ , Cu 2+ The positive electrode active material is a layered oxide material, which can have a higher gram capacity and compaction density, and is helpful to improve the capacity of the sodium ion battery.

[0034] The particle size of the positive electrode active material 113 ranges from 1 to 20 μm, for example, 1 μm, 2 μm, 3 μm, 5 μm, 7 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, or 20 μm. The median particle size D50 of the positive electrode active material 113 is 1 The particle size of the sample is 4-15 μm, for example, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm. D50 refers to the particle size corresponding to when the cumulative particle size distribution percentage in the sample reaches 50%.

[0035] Continue to refer to Figure 2 Compared with the positive electrode active material, the stabilizer 114 is a small particle material, and its particle size is smaller than that of the positive electrode active material 113. The median particle size D50 of the stabilizer 114 is 2 The value range of is 0.2-2 μm. The stabilizer 114 is filled between the particles of the positive electrode active material 113. A network structure is formed between the stabilizer 114 and the positive electrode active material 113 to improve the conductivity of the positive electrode material layer. The molecular structure of the stabilizer 114 contains (XO 4 ) n- wherein X is selected from at least one of P, S, or Si. For example, the stabilizer 114 may be selected from Na 2 Fe 2 (SO 4 ) 3 、Na 2 MSiO 4 、NaFePO 4 、Na 2 FeP 2 O 7 、Na4 Fe 2 (PO 4 ) 2 P 2 O 7 、Na 3 V 2 Fe(PO 4 ) 3 、Na 3 V N 2 Fe(PO 4 ) 3 、Na 3 VTiFe(PO 4 ) 3 、Na 3 Fe 2 Fe(PO 4 ) 3 、Na 3 MnTiFe(PO 4 ) 3 The stabilizer has a charge-discharge curve behavior similar to that of the sodium ion layered oxide material and can form a continuous conductive network to improve the conductivity and capacity of the composite positive electrode material. The median particle size D50 of the stabilizer 114 is 2 Less than or equal to the median particle size D50 of the positive electrode active material 1 30%. Among them, the molecular structure of stabilizer 114 includes (XO 4 ) n- In addition to the groups, transition metal ion bonds may also be included to assist in enhancing the stability of the conductive network formed between the positive electrode active material and the stabilizer. Wherein, the atomic percentage of X in the composite positive electrode material is 1% to 15%, for example, it can also be 1% to 10%. The atomic percentage of X in the composite positive electrode material is typically but not limited to 1%, 2%, 4%, 5%, 6%, 8%, 10%, 12%, 13%, 14% or 15%.

[0036] In one embodiment, the gram capacity of the stabilizer is ≥ 60% of the gram capacity of the positive electrode active material, and the median voltage of the stabilizer is within the range of ±15% of the median voltage of the positive electrode active material.

[0037] In one embodiment, the mass proportion of the stabilizer in the composite positive electrode material is 1% to 40%. Exemplarily, the mass proportion of the stabilizer in the composite positive electrode material may be, for example, 1%, 3%, 5%, 8%, 10%, 12%, 15%, 17%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 37% or 40%.

[0038] In one embodiment, the median voltage of the composite positive electrode material is greater than 3.0 V, the gram capacity of the composite positive electrode material is greater than 120.0 mAh / g, the compaction density of the composite positive electrode material is greater than 3.0 g / cc, and the film resistivity of the composite positive electrode material is 5 Ω*cm to 30.0 Ω*cm.

[0039] The composite positive electrode material of the present application will be specifically explained below in combination with embodiments and comparative examples.

[0040] Example 1

[0041] This embodiment provides a composite positive electrode material, which is obtained by the following method:

[0042] Step S11: 2 CO 3 、Ni(OH) 2 , Fe 2 O 3 、MnO 2 The materials were weighed in a molar ratio of 1:1 / 3:1 / 3:1 / 3, dissolved and mixed evenly with deionized water, and then dried. The materials were sintered at 900-1000°C in a compressed air atmosphere for 20 hours to obtain layered oxide Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 Materials. Layered oxide Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 Median particle size D50 of the material 1 It is 6.5μm.

[0043] Step S12: small particles of stabilizer Na 4 Fe 2 (PO 4 ) 2 P 2 O 7 and layered oxides Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 The composite positive electrode material M1 was obtained by high-energy ball milling at a mass ratio of 1:9. 1 Prepare slurry and coat it on the surface of aluminum foil to obtain positive electrode sheet. Stabilizer Na 3 Fe 2 (PO 4 ) 2 O 7 Median particle size D50 2 It is 1.9μm.

[0044] Example 2

[0045] This embodiment provides a composite positive electrode material, which is obtained by the following method:

[0046] Step S21: Na 2 CO 3 、Ni(OH) 2 , Fe 2 O 3 、MnO 2 The materials were weighed in a molar ratio of 1:1 / 3:1 / 3:1 / 3, dissolved and mixed evenly with deionized water, and then dried. The materials were sintered at 900-1000°C in a compressed air atmosphere for 20 hours to obtain layered oxide Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 Materials. Layered oxide Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 Median particle size D50 of the material 1 It is 6.5μm.

[0047] Step S22: small particles of stabilizer Na 4 Fe 2 (PO 4 ) 2 P 2 O 7 and layered oxides Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 The composite positive electrode material M2 was obtained by high-energy ball milling at a mass ratio of 2:8. 2 Prepare the slurry and coat it on the surface of aluminum foil to obtain the positive electrode sheet. Stabilizer Na 4 Fe 2 (PO 4 ) 2 P 2 O 7 Median particle size D50 2 It is 1.9μm.

[0048] Example 3

[0049] This embodiment provides a composite positive electrode material, which is obtained by the following method:

[0050] Step S31: 2 CO 3、Ni(OH) 2 , Fe 2 O 3 、MnO 2 The materials were weighed in a molar ratio of 1:1 / 3:1 / 3:1 / 3, dissolved and mixed evenly with deionized water, and then dried. The materials were sintered at 900-1000°C in a compressed air atmosphere for 20 hours to obtain layered oxide Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 Materials. Layered oxide Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 Median particle size D50 of the material 1 It is 6.5μm.

[0051] Step S32: small particles of stabilizer Na 4 Fe 2 (PO 4 ) 2 P 2 O 7 and layered oxides Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 The composite cathode material M was obtained by high-energy ball milling at a mass ratio of 2:8 and mixing uniformly. 3 Then, the composite positive electrode material M3 is used to prepare a slurry, which is coated on the surface of the aluminum foil to obtain a positive electrode sheet. Stabilizer Na 3 Fe 2 (PO 4 ) 2 O 7 Median particle size D50 2 It is 1.9μm.

[0052] Example 4

[0053] This embodiment provides a composite positive electrode material, which is obtained by the following method:

[0054] Step S41: 2 CO 3 、Ni(OH) 2 , Fe 2 O 3 、MnO 2 The materials were weighed in a molar ratio of 1:1 / 3:1 / 3:1 / 3, dissolved and mixed evenly with deionized water, and then dried. The materials were sintered at 900-1000°C in a compressed air atmosphere for 20 hours to obtain layered oxide Na(Ni 1 / 3 Fe1 / 3 Mn 1 / 3 ) 2 Materials. Layered oxide Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 Median particle size D50 of the material 1 It is 7.5μm.

[0055] Step S42: small particles of stabilizer Na 2 MnSiO 4 and layered oxides Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 The composite cathode material M was obtained by high-energy ball milling at a mass ratio of 2:8 and mixing uniformly. 4 Then, the composite positive electrode material M4 was used to prepare a slurry, which was coated on the surface of the aluminum foil to obtain a positive electrode sheet. Stabilizer Na 3 Fe 2 (PO 4 ) 2 O 7 Median particle size D50 2 is 2.0μm.

[0056] Example 5

[0057] This embodiment provides a composite positive electrode material, which is obtained by the following method:

[0058] Step S41: 2 CO 3 、Ni(OH) 2 , Fe 2 O 3 、MnO 2 The materials were weighed in a molar ratio of 1:1 / 3:1 / 3:1 / 3, dissolved and mixed evenly with deionized water, and then dried. The materials were sintered at 900-1000°C in a compressed air atmosphere for 20 hours to obtain layered oxide Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 Materials. Layered oxide Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 Median particle size D50 of the material 1 It is 11.2μm.

[0059] Step S42: small particles of stabilizer Na 2 Fe 2 (SO4 ) 3 and layered oxides Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 The composite cathode material M was obtained by high-energy ball milling at a mass ratio of 2:8 and mixing uniformly. 5 Then, the composite positive electrode material M5 was used to prepare a slurry, which was coated on the surface of the aluminum foil to obtain a positive electrode sheet. Stabilizer Na 3 Fe 2 (PO 4 ) 2 O 7 Median particle size D50 2 is 2.5μm.

[0060] Example 6

[0061] This embodiment provides a composite positive electrode material, which is obtained by the following method:

[0062] Step S41: 2 CO 3 、Ni(OH) 2 , Fe 2 O 3 、MnO 2 The materials were weighed in a molar ratio of 1:1 / 3:1 / 3:1 / 3, dissolved and mixed evenly with deionized water, and then dried. The materials were sintered at 900-1000°C in a compressed air atmosphere for 20 hours to obtain layered oxide Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 Materials. Layered oxide Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 Median particle size D50 of the material 1 It is 7.5μm.

[0063] Step S42: small particles of stabilizer Na 3 V 2 Fe(PO 4 ) 3 and layered oxides Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 The composite cathode material M was obtained by high-energy ball milling at a mass ratio of 2:8 and mixing uniformly. 6 Then, the composite positive electrode material M6 was used to prepare a slurry, which was coated on the surface of the aluminum foil to obtain a positive electrode sheet. Stabilizer Na 3 Fe2 (PO 4 ) 2 O 7 Median particle size D50 2 2.2μm.

[0064] Comparative Example 1

[0065] This embodiment provides a positive electrode material, which is obtained by the following method: 2 CO 3 、Ni(OH) 2 , Fe 2 O 3 、MnO 2 The materials were weighed in a molar ratio of 1:1 / 3:1 / 3:1 / 3, dissolved and mixed evenly with deionized water, and then dried. They were sintered at 900-1000°C in a compressed air atmosphere for 20 hours to obtain Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 The positive electrode material is then used to prepare a slurry, which is then coated on the surface of an aluminum foil to obtain a positive electrode sheet.

[0066] Comparative Example 2

[0067] This embodiment provides a composite positive electrode material, which is obtained by the following method:

[0068] Step S21: Na 2 CO 3 、Ni(OH) 2 , Fe 2 O 3 、MnO 2 The materials were weighed in a molar ratio of 1:1 / 3:1 / 3:1 / 3, dissolved and mixed evenly with deionized water, and then dried. They were sintered at 900-1000°C in a compressed air atmosphere for 20 hours to obtain Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 Material.

[0069] Step S22: NaH 2 PO 4 The transition metal hydroxide nanoparticles are ball-milled with the transition metal sodium oxide prepared in step S21, and heated to 500-550° C. under a nitrogen protective atmosphere to obtain an island-shaped coated positive electrode material, which is recorded as M8.

[0070] Comparative Example 3

[0071] This embodiment provides a composite positive electrode material, which is obtained by the following method:

[0072] Step S21: Na 2 CO 3 、Ni(OH) 2 , Fe 2 O 3 、MnO 2 The materials were weighed in a molar ratio of 1:1 / 3:1 / 3:1 / 3, dissolved and mixed evenly with deionized water, and then dried. The materials were sintered at 900-1000°C in a compressed air atmosphere for 20 hours to obtain layered oxide Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 Material.

[0073] Step S22: small particles of stabilizer Na 4 Fe 2 (PO 4 ) 2 P 2 O 7 and layered oxides Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 The composite cathode material M was obtained by high-energy ball milling at a mass ratio of 1:1 and mixing uniformly. 8 Then, the composite positive electrode material M9 was used to prepare a slurry, which was coated on the surface of the aluminum foil to obtain a positive electrode sheet.

[0074] Comparative Example 4

[0075] This embodiment provides a composite positive electrode material, which is obtained by the following method:

[0076] Step S21: Na 2 CO 3 、Ni(OH) 2 , Fe 2 O 3 、MnO 2 The materials were weighed in a molar ratio of 1:1 / 3:1 / 3:1 / 3, dissolved and mixed evenly with deionized water, and then dried. The materials were sintered at 900-1000°C in a compressed air atmosphere for 20 hours to obtain layered oxide Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 Materials. Layered oxide Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2Median particle size D50 of the material 1 It is 6.5μm.

[0077] Step S22: small particles of stabilizer Na 4 Fe 2 (PO 4 ) 2 P 2 O 7 and layered oxides Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 The composite cathode material M was obtained by high-energy ball milling at a mass ratio of 1:1 and mixing uniformly. 9 Then, the composite positive electrode material M10 was used to prepare a slurry, which was coated on the surface of the aluminum foil to obtain a positive electrode sheet. Stabilizer Na 4 Fe 2 (PO 4 ) 2 P 2 O 7 Median particle size D50 2 is 4.0μm.

[0078] The positive electrode sheets of Examples 1-6 and Comparative Examples 1-4, the sodium metal counter electrode, the glass fiber separator, and 1M NaPF 6 The CR2032 button-type sodium ion battery was assembled in an argon glove box using dimethyl ether as the electrolyte. The rate discharge capacity retention rate and the capacity retention rate after 300 cycles of the sodium ion battery corresponding to each positive electrode were tested respectively. The test results are listed in Table 1.

[0079] Table 1

[0080]

[0081] It can be seen from the relevant data in Table 1 that the sodium ion batteries corresponding to Examples 1-6 of the present application can have a higher capacity retention rate under high current discharge conditions of 2C and 3C, while the capacity retention rate of the sodium ion batteries corresponding to Comparative Examples 1-4 is relatively low. Among them, it can be seen from the relevant data of Example 1 and Comparative Example 1 that when the positive electrode material does not contain a stabilizer, the corresponding high current discharge capacity retention rate is significantly reduced, especially under 3C discharge conditions, the capacity retention rate is reduced by about 80%. The capacity retention rate of the sodium ion battery of Example 1 of the present application is still above 85%. The sodium ion battery corresponding to the composite positive electrode material of Example 1 has a capacity retention rate of 97.5% after 300 cycles at 45°C and 0.5C. Compared with the sodium ion battery corresponding to the positive electrode material of Comparative Example 1, the capacity retention rate after 300 cycles at 0.5C is 92.0%, an increase of 6.0%, and the 3C high rate discharge capacity is increased by 8.0%.

[0082] From the comparison data of Example 2 and Comparative Example 2, it can be seen that when island-shaped coating exists, the battery rate performance is reduced.

[0083] From the comparison data of Example 2 and Comparative Example 3, it can be seen that when the content of the stabilizer is high, an island-shaped coating layer is easily formed, which is not conducive to the formation of a conductive network. Therefore, relative to the data of Example 2, the large current discharge capacity retention rate and cycle capacity retention rate of Comparative Example 3 are both lower.

[0084] From the comparison data of Example 2 and Comparative Example 4, it can be seen that when the relationship between the particle size of the stabilizer and the positive electrode active material does not meet the conditions specified in the present application, that is, when the particle size of the stabilizer is larger, a dense conductive network cannot be formed in the obtained composite positive electrode material, and therefore, the improvement of the large current discharge capacity retention rate and the cycle capacity retention rate is not utilized.

[0085] in, Figure 3 is a cross-sectional scanning morphology photograph of the composite positive electrode material of Example 1; Figure 3 As shown, the composite positive electrode material of the embodiment of the present application has a relatively dense structure, and the stabilizer and the positive electrode active material form a graded relationship, thereby forming a stable conductive network, which helps to improve the conductivity of the composite positive electrode material. Figure 4 This is the energy spectrum mapping diagram of the composite positive electrode material of Example 1. The length and width of the test area are 50μm*30μm respectively, the test voltage is 15kV, and the scanning time is 300s. Figure 4 As shown, it can be seen from the energy spectrum that the composite positive electrode material of the embodiment of the present application contains elements such as F, Na, P, Mn, Fe, Ni, etc. Among them, the atomic percentage of P in the composite positive electrode material is 4.5%.

[0086] Figure 5 This is the charge and discharge curve of the positive electrode material in Comparative Example 1. Figure 6 Na is the stabilizer 4 Fe 2 (PO 4 ) 2 P 2 O 7 Charge and discharge curve diagram. Figure 5 and Figure 6 As shown, the positive electrode material Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 2 and stabilizer Na 4 Fe 2 (PO 4 ) 2 P 2 O 7The charge and discharge curves are relatively consistent and can have similar electrochemical windows, reducing the negative impact of stabilizers on the positive electrode materials. Figure 7 The charge and discharge curves of the composite positive electrode material of Example 1 and the positive electrode material of Comparative Example 1 are shown in FIG. Figure 7 It can be seen that the charge and discharge curve of the sodium ion battery corresponding to Example 1 is similar to the charge and discharge curve of the positive electrode material of Comparative Example 1, which can help reduce the charge and discharge polarization of the positive electrode material and help improve the battery rate performance and cycle stability. Figure 8 The following is a graph showing the cycle capacity retention rate of the sodium ion battery corresponding to Examples 1-3 and Comparative Example 1 at 45°C and 0.5C. Figure 8 As shown, the cycle life of the sodium ion battery of the embodiment of the present application is higher than that of comparative example 1, and the sodium ion battery of the embodiment of the present application can have higher cycle stability under high temperature environment.

[0087] In summary, the composite positive electrode material of the embodiment of the present application can help improve the high current charge and discharge capacity retention rate and cycle life of the sodium ion battery. The composite positive electrode material of the layered oxide mixed stabilizer can improve the cycle life of the battery in a high temperature environment. The preparation method is simple, and can improve the material stability, increase the cycle life, and improve the high rate discharge capacity.

[0088] Based on the same technical purpose, the present application provides a battery pack, which includes multiple batteries, and the multiple batteries are connected in series or in parallel; the battery is a sodium ion battery of an embodiment of the present application.

[0089] Based on the same technical purpose, the present application provides an energy storage system, which includes a power converter and at least one battery pack of the third aspect of the present application; the power converter is used to convert the voltage output by the battery pack into power and output it to a power grid or a load, and / or, to convert the voltage output by an external power supply into power and output it to the battery pack.

[0090] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A sodium ion battery, characterized in that: The invention comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a composite positive electrode material; the composite positive electrode material comprises a positive electrode active material and a stabilizer, the positive electrode active material is a sodium ion layered oxide, the stabilizer is filled between particles of the positive electrode active material, the particle size of the stabilizer is smaller than the particle size of the positive electrode active material, and the molecular structure of the stabilizer contains (XO4) n- Group; Wherein, X is selected from at least one of P, S, or Si, and the atomic percentage of X in the composite positive electrode material is 1% to 15%.

2. The sodium ion battery according to claim 1, characterized in that The median particle size D502 of the stabilizer is less than or equal to 30% of the median particle size D501 of the positive electrode active material.

3. The sodium ion battery according to claim 1 or 2, characterized in that ,The sodium ion battery according to claim 1 is characterized in that the stabilizer is selected from at least one of Na2Fe2(SO4)3, Na2MnSiO4, NaFePO4, Na2FeP2O7, Na3Fe2(PO4)P2O7, Na4Fe2(PO4)2P2O7, Na3V2Fe(PO4)3, Na3VMn2Fe(PO4)3, Na3VTiFe(PO4)3, Na3Fe2Fe(PO4)3, and Na3MnTiFe(PO4)3.

4. The sodium ion battery according to any one of claims 1 to 3, characterized in that: The median particle size D502 of the stabilizer is in the range of 0.2-2 μm.

5. The sodium ion battery according to any one of claims 1 to 4, characterized in that: The gram capacity of the stabilizer is ≥ 60% of the gram capacity of the positive electrode active material, and the median voltage of the stabilizer is within a range of ±15% of the median voltage of the positive electrode active material.

6. The sodium ion battery according to any one of claims 1 to 5, characterized in that: The stabilizer accounts for 1% to 40% by mass in the composite positive electrode material.

7. The sodium ion battery according to any one of claims 1 to 6, characterized in that: The median voltage of the composite positive electrode material is greater than 3.0V.

8. The sodium ion battery according to any one of claims 1 to 7, characterized in that: The gram capacity of the composite positive electrode material is greater than 120.0 mAh / g.

9. The sodium ion battery according to any one of claims 1 to 8, characterized in that: The compaction density of the composite positive electrode material is >3.0 g / cc.

10. The sodium ion battery according to any one of claims 1 to 9, characterized in that: The film resistivity of the composite positive electrode material is 5Ω*cm to 30.0Ω*cm.

11. The sodium ion battery according to any one of claims 1 to 10, characterized in that: The molecular formula of the positive electrode active material is Na z Ni x M y O2, wherein x+y=1, 0.9≤z≤1.1, and M is selected from Fe 2+ , Mn 3+ , Ca 2+ 、Zn 2+ Mg 2+ 、Ti 3+ 、Al 3+ , Cu 2+ At least one of them.

12. The sodium ion battery according to any one of claims 1 to 11, characterized in that: In the differential scanning calorimeter spectrum of the composite positive electrode material, the position of the exothermic peak of the composite positive electrode material is greater than 300°C.

13. A battery pack, characterized in that: The battery pack comprises a plurality of batteries, and the plurality of batteries are connected in series or in parallel; the battery is a sodium ion battery as described in any one of claims 1 to 12.

14. An energy storage system, characterized in that: The energy storage system includes a power converter and at least one battery pack as described in claim 13; the power converter is used to convert the voltage output by the battery pack into power and output it to a power grid or a load, and / or to convert the voltage output by an external power supply into power and output it to the battery pack.

Citation Information

Patent Citations

  • Positive plate, preparation method thereof and sodium ion battery

    CN115799447A